Interleukin-6 (IL-6) influence on colonic anastomosis healing in rats - Greca,Fernando Hintz (2007)
PURPOSE:To observe the effect of pro-inflamatory citokin, Interleukin-6 (IL-6), administration on the healing of colonic anastomosis in rats. METHODS: Thirty Wistar rats were divided into 2 groups of 15 animals each: a control group and an experiment group. The animals of the experiment group were submitted to injection of 500µg/kg of IL-6 Recombinant (Sandoz Phamarceutical®) subcutaneously 24 and 12 hours preceding the surgery, and the control group, were submitted to the injection of saline solution, using the same volume of solution as well as the way of administration. The rats were submitted to an end to end colonic anastomosis, being sacrificed in the 7th post-operative day, the site of the anastomosis was evaluated regarding to the adhesions that was quantified and the presence of complications was observed. The colon containing the anastomosis was submitted to a tensiometric study and a sample were sent for histological studies with HE and Sirius Red dye. RESULTS: The macroscopic and the tensiometric study did not demonstrate any significant differences between the control and experiment group. Regarding the histological evaluation, there was a significant reduction of the chronic inflammatory process in the experiment group (p=0,0209) and a lesser granulation area (p=0,0099). The total amount of collagen was similar in both groups, however, the experimental group showed a predominant area of immature collagen (p=0.009). CONCLUSIONS: The longer persistence of the acute phase of wound healing in the experiment group, as well as a decreased of the mature collagen type I, demonstrating that the IL-6 was harmful to the colonic healing anastomosis in rats.